Implementasi Media Audio Visual Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fikih - Badruttamam, Choirul Anwar; Kholidah, Dwi Rosyidatul (ELEMENTARY : Journal of Primary Education, 2023)
In this study the aims were to describe the application, to find out the learning outcomes of students and to find out what are the advantages of audio-visual learning media in Islamic jurisprudence subjects at MI Darul Ulum Pedagang. The approach used in this study is a descriptive qualitative approach. The reason for using this type of descriptive qualitative research is because the researcher wants to review the real and what it is about the implementation of Audio Visual Media to Improve Student Learning Outcomes in Jurisprudence Subjects. The results of this study are 1) The application of audio-visual media to the fiqh subject at MI Darul Ulum Pedagang requires some careful preparation from before, starting from the preparatory stage, the implementation stage of the learning process and the final stage, namely the stage of making conclusions and questions as a starting point. measure learning success. 2) The successful application of audio-visual (video) learning media can be identified by measuring learning outcomes. One of the things teachers can do to measure student learning outcomes is by giving pre-tests and post-tests. 3) Some of the advantages of audio-visual media, namely, increasing / increasing students' learning motivation, students can observe, perform, demonstrate, and can understand the material as a whole. Students don't get bored quickly and teachers don't run out of steam. The use of audio-visual media can create a different learning atmosphere, which means it can create innovative learning, besides that students can also understand the flow of material presented even without explanation or words from the teacher.